2016
DOI: 10.18632/oncotarget.7014
|View full text |Cite
|
Sign up to set email alerts
|

WISP-1 promotes VEGF-C-dependent lymphangiogenesis by inhibiting miR-300 in human oral squamous cell carcinoma cells

Abstract: Oral squamous cell carcinoma (OSCC), which accounts for nearly 90% of head and neck cancers, is characterized by a poor prognosis and a low survival rate. Vascular endothelial growth factor-C (VEGF-C) has been implicated in lymphangiogenesis and is correlated with cancer metastasis. WNT1-inducible signaling pathway protein-1 (WISP)-1/CCN4 is an extracellular matrix-related protein that belongs to the CCN family and stimulates many biological functions. Our previous studies showed that WISP-1 plays an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…WISP1 promotes angiogenesis via VEGF‐A expression in oral squamous cell carcinoma cells . The protein might be a potential target to prevent metastasis and lymphangiogenesis in human oral squamous cell carcinoma cells . Investigators demonstrated that the expression of WISP1 in HNSCC was significantly higher compared to normal tissue, suggesting that WISP1 expression might correlate with tumour progression .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WISP1 promotes angiogenesis via VEGF‐A expression in oral squamous cell carcinoma cells . The protein might be a potential target to prevent metastasis and lymphangiogenesis in human oral squamous cell carcinoma cells . Investigators demonstrated that the expression of WISP1 in HNSCC was significantly higher compared to normal tissue, suggesting that WISP1 expression might correlate with tumour progression .…”
Section: Discussionmentioning
confidence: 99%
“…40 The protein might be a potential target to prevent metastasis and lymphangiogenesis in human oral squamous cell carcinoma cells. 21 Investigators demonstrated that the expression of WISP1 in HNSCC was significantly higher compared to normal tissue, suggesting that WISP1 expression might correlate with tumour progression. 41 In a large study by Van Kempen et al comprising a cohort of oral and oropharyngeal cancers with known HPV status, CNAs and survival, WISP1 turned out to be a predictor for worse disease-free survival in oral and oropharyngeal squamous cell carcinoma, independent of HPV status.…”
Section: Data Of Various Groups Have Demonstrated An Overexpression Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…After trypsinization, sections were blocked by incubation in 3% FBS in PBS. The primary antibody anti-human CCL5, VEGF-C or LYVE-1 was applied to the slides at a dilution from 1:50 to 1:150 and incubated at 4°C overnight [45]. After the slides were washed 3 times with PBS, the samples were treated with the secondary antibody at a dilution of 1:100.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work revealed that miR-323a-3p, miR-433 and miR-409 transcribed from this cluster acted as tumor suppressors [16][17][18]. miR-300, belonging to the DLK1-DIO3 miRNA cluster, was previously reported to be associated with human osteosarcoma, pancreatic cancer, non-small cell lung cancer, glioblastoma, and oral squamous cell carcinoma [20][21][22][23][24]. However, to the best of our knowledge, the role miR-300 in BCa and its mechanism remains unresolved.…”
Section: Introductionmentioning
confidence: 99%